2022
DOI: 10.3389/fnbeh.2022.828782
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Demographic and Pharmacological Factors in Alzheimer Patients With Dementia and Cognitive Impairments

Abstract: ObjectiveThe current study investigates sex differences associated with pharmacological and demographic characteristics in Alzheimer patients (AD) with dementia (ADD) or mild cognitive impairment (MCI).MethodA retrospective analytical approach was used to analyze data from 45,696 AD patients with MCI or ADD. The univariate analysis was used to determine differences in demographic, and pharmacological characteristics for male and female ADD and MCI-AD patients. Multivariate analysis was used to predict specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Total events Heterogeneity: Chi 2 = 3.36, df = 5 (P = 0.64); I 2 = 0% Test for overall effect: Z = 1.38 (P = 0.17) Test for subgroup differences: Chi 2 = 0.02, df = 2 (P = 0.99); I 2 = 0% Computational and Mathematical Methods in Medicine receptors, as well as dopamine and choline. It can antagonize and even selectively reduce the firing of dopaminergic neurons in the limbic system (A10), while having little effect on the motor function pathway of the striatum (A9) [25][26][27]. Meta-analysis showed that the clinical efficacy was similar and there was no significant difference between olanzapine and clozapine in the treatment of mental and behavioral disorders in patients with AD.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…Total events Heterogeneity: Chi 2 = 3.36, df = 5 (P = 0.64); I 2 = 0% Test for overall effect: Z = 1.38 (P = 0.17) Test for subgroup differences: Chi 2 = 0.02, df = 2 (P = 0.99); I 2 = 0% Computational and Mathematical Methods in Medicine receptors, as well as dopamine and choline. It can antagonize and even selectively reduce the firing of dopaminergic neurons in the limbic system (A10), while having little effect on the motor function pathway of the striatum (A9) [25][26][27]. Meta-analysis showed that the clinical efficacy was similar and there was no significant difference between olanzapine and clozapine in the treatment of mental and behavioral disorders in patients with AD.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…ChEIs reduce the breakdown of acetylcholine in the brain, preserving cognitive functions and improving the cognitive, behavioral, and neuropsychiatric symptoms of AD ( Coker-Ayo et al ., 2022 ). Patients diagnosed with mild-to-moderate AD are prescribed galantamine, rivastigmine, and/or donepezil as first-line therapeutics ( Calabria et al ., 2009 ).…”
Section: Sex Differences In the Effects Of Therapeutics On Dementiamentioning
confidence: 99%
“…Galantamine is also used to treat mild cognitive impairment (MCI) in Hispanic men, while it is used to treat MCI-AD in African-American women. These differences in sex demographics and ethnicity highlight the importance of tailoring treatment for patients diagnosed with AD ( Coker-Ayo et al ., 2022 ).…”
Section: Sex Differences In the Effects Of Therapeutics On Dementiamentioning
confidence: 99%
“…Notably, more women are affected by dementia than men. Overall, twice as many women have dementia compared to Alzheimer’s disease [ 2 ]. Menopause affects the secretion of sex hormones in women, such as progesterone, testosterone, and estrogen levels, which increases the risk of dementia in menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause affects the secretion of sex hormones in women, such as progesterone, testosterone, and estrogen levels, which increases the risk of dementia in menopausal women. Based on estrogen and progestin medroxyprogesterone acetate, researchers have proposed the “healthy cell hypothesis” in which estradiol exerts neuroprotective effects [ 2 , 3 ]. Dementia is a neurodegenerative process that affects memory, social behavior, activities of daily living, and sleep; reduced nocturnal parasympathetic activity may represent early predictive factors for progression to dementia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%